CONTRIBUTION ANALYSIS OF RESERVATION THROUGH TRAVEL AGENT TO ROOM OCCUPANCY AT GRAND ZURI KUTA BALI HOTEL - Ni Luh Yuni Kusuma Yanti; Ni Made Ernawati; Ni Ketut Bagiastuti (Journal of Applied Sciences in Travel and Hospitality, 2018)
Travel agent is a business engaged in the field of service and provides information about all things related to travel. The purpose of this research is to know the amount of travel agent contribution to room occupancy at Grand Zuri Kuta Bali Hotel and to know which travel agent dominatly contribute to room occupancy at Grand Zuri Kuta Bali. The data used is reservation data through travel agent, other reservation source data (online travel agent, direct reservation, corporate and government) and room occupancy of the data in 2015 until 2017. Data in this research is obtained in data collection method that though interview and documentation. Data analysis technique used is quantitative descriptive analysis technique. Based on the results of this research show that, reservation through travel agent does have a great contribution to room occupancy at Grand Zuri Kuta Bali Hotel that is equal to 48.41% and 51.59% influenced by factors other factors not examined in this research while the most dominant travel agent contribution to room occupancy at Grand Zuri Kuta Bali Hotel is Tjendana Mandra Ssakti (TMS) Tour & Travel with contribution of 10.93%.